(untitled) (Research, Society and Development, 2020)
The economic and social development of a nation depends, among other variables, on the diffusion of technology from macro levels to micro operations levels. The aim of this paper is to illustrate the application of production planning and control knowledge in a micro operation of rubber artifacts. For this, the current production process was analyzed through internal records and interviews with company managers in order to propose a better organization of the items needed for production and their processing times. The main contribution of this work is the application of the material planning logic in a specific context, as well as the exercise of outlining important parameters for production control.